2013
DOI: 10.1111/sms.12119
|View full text |Cite
|
Sign up to set email alerts
|

A 1‐year prospective analysis of injuries in amateur and elite fistball

Abstract: The purpose of this study was to examine the incidence and mechanisms of acute injuries in the sport of fistball. No scientific studies on injury characteristics have yet been conducted in this traditional sport game. The study was conducted prospectively over the course of 12 months. During a total of 40.308 h of sport-specific exposure, 240 players reported 492 injuries, representing an overall injury rate of 12.2 injuries/1000 h of exposure. Most injuries were classified as bagatelle injuries (67.8%). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The progressive professionalization in fistball and the increasing popularity of this sport in many countries should be reflected in the future by a stronger interest from sport science. This study as well as the work of [ 4 , 5 , 6 , 7 ] are a starting point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The progressive professionalization in fistball and the increasing popularity of this sport in many countries should be reflected in the future by a stronger interest from sport science. This study as well as the work of [ 4 , 5 , 6 , 7 ] are a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…The field of sport science, however, has paid little attention to fistball so far and very few scientific papers on the topic are available. Besides older publications on methodological aspects (e.g., [ 2 , 3 ]), studies often deal with the risk of injury in fistball [ 4 , 5 ]. Runer et al [ 5 ], for example, found over the course of 12 months an overall injury rate of 12.2 injuries/1000 h of exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for the prevention of sports injury, but when the damage appears, how to expand the scope of treatment is also an important measure to avoid the damage in amateur sports, athletes or instructors should grasp the basic method of health care, such as in the face of the body abrasion, should be timely with saline wash the wound, wound around with 75% alcohol disinfection and if the wound is deep, serious pollution should be injected tetanus, the only way to ensure the effectiveness of prevention system. [7] …”
Section: Amateur Sports Training In How To Prevent Sports Injurymentioning
confidence: 99%